1997
DOI: 10.1097/00001756-199701200-00023
|View full text |Cite
|
Sign up to set email alerts
|

Acute administration of the CB1 cannabinoid receptor antagonist SR 141716A induces anxiety-like responses in the rat

Abstract: Animal models have revealed that psychoactive cannabinoids induce both anxiolytic and anxiety-like reactions which are dose- and context-dependent. In the present study we examined the acute actions of the CB1 cannabinoid receptor antagonist SR 141716A in both the defensive withdrawal test and the elevated plus-maze in rats. Acute administration of SR 141716A (0.1, 1 and 3 mg kg-1) induced defensive responses in both anxiety tests, at a dose of 3 mg kg-1. This dose had no effect on horizontal locomotor activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
181
3
6

Year Published

2000
2000
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 277 publications
(202 citation statements)
references
References 1 publication
11
181
3
6
Order By: Relevance
“…In rats, for example, a single electric shock to the paw elevates anandamide levels in the midbrain (Hohmann et al, 2005), while in mice physical restraint decreases anandamide levels in the amygdala (Patel et al, 2004). Moreover, pharmacological blockade or genetic ablation of CB 1 receptors exacerbates normal reactions to acute stress, presumably by disabling an endocannabinoid modulation of these reactions (Navarro et al, 1997;Haller et al, 2004;Urigüen et al, 2004). Finally, the FAAH inhibitor URB597 enhances stress-coping behaviors in a rimonabant-sensitive manner (Kathuria et al, 2003;Gobbi et al, 2005), suggesting that anandamide interacts with a subgroup of CB 1 receptors in the brain that regulate stress responses.…”
Section: Discussionmentioning
confidence: 99%
“…In rats, for example, a single electric shock to the paw elevates anandamide levels in the midbrain (Hohmann et al, 2005), while in mice physical restraint decreases anandamide levels in the amygdala (Patel et al, 2004). Moreover, pharmacological blockade or genetic ablation of CB 1 receptors exacerbates normal reactions to acute stress, presumably by disabling an endocannabinoid modulation of these reactions (Navarro et al, 1997;Haller et al, 2004;Urigüen et al, 2004). Finally, the FAAH inhibitor URB597 enhances stress-coping behaviors in a rimonabant-sensitive manner (Kathuria et al, 2003;Gobbi et al, 2005), suggesting that anandamide interacts with a subgroup of CB 1 receptors in the brain that regulate stress responses.…”
Section: Discussionmentioning
confidence: 99%
“…CCK has been shown to enhance memory formation by acting on hippocampal neurons, and have strong anxiogenic effects, whereas cannabinoids interfere with memory formation and the endogenous tone they mediate may alleviate anxiety. 17,32,37,41 One may argue that the magnitude of suppression of GABA release (ϳ50%) is much higher than the number of CCK-containing interneurons in the hippocampus estimated to represent only 10-20% of all hippocampal interneurons in the rat. Indeed, not all CB1-containing interneurons expressed CCK (see Table 1 for details).…”
Section: Cb1 Cannabinoid Receptor Activation Leads To a Reduction Of mentioning
confidence: 99%
“…Indeed, it has been clearly demonstrated that cannabinoid signaling is involved in the control of anxiety, albeit it has been difficult to define the exact role of this signaling. In particular, both anxiolytic-and anxiogenic-like effects have been reported by using cannabinoid receptor agonists at low and high doses, respectively [14], and also by CB1 receptor antagonists [15,16]. These opposite observations might be explained by the distribution of CB1 receptors in the brain.…”
Section: Discussionmentioning
confidence: 99%